1978
DOI: 10.3402/tellusa.v30i1.10319
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal trends of NH<sup>+</sup><sub>4</sub> and NO<sup>-</sup><sub>3</sub> nitrogen isotope composition in rain collected at Jülich, Germany

Abstract: Data are presented on nitrogen isotope. composition in ammonium and nitrate from rain-water collected over 2 years in an interior area at Jiilich, Germany. The seasonal trends in these data are discussed relative to natural and anthropogenic emissions of nitrogen compounds which additionally have been measured or estimated in their isotope composition, e.g. ammonia from animal urine, fuel combustion, fertilizer use and organic soil nitrogen, and natural and anthropogenic nitric oxides from automobile exhausts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
149
2
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 27 publications
18
149
2
1
Order By: Relevance
“…However, this isotope effect does not provide an adequate explanation for the observed seasonal changes in d 15 N of NO 3 À at Summit , Ny Å lesund [Heaton et al, 2004], or Bermuda [Hastings et al, 2003]. In fact, recent calculations using this isotope effect and the assumptions made in the Freyer et al [27] Several studies suggest that the d 15 N of NO 3 À most likely reflects the N isotopic composition of NO x sources [Freyer, 1978[Freyer, , 1991Garten, 1996;Russell et al, 1998;Xiao and Liu, 2002;Hastings et al, 2003;Heaton et al, 2004]. The important pre-industrial sources of NO x include biomass burning, biogenic soil emissions, lightning, and stratospheric injection [e.g., Wolff, 1995;Legrand and Kirchner, 1990].…”
Section: No 3 à à à Scavengingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this isotope effect does not provide an adequate explanation for the observed seasonal changes in d 15 N of NO 3 À at Summit , Ny Å lesund [Heaton et al, 2004], or Bermuda [Hastings et al, 2003]. In fact, recent calculations using this isotope effect and the assumptions made in the Freyer et al [27] Several studies suggest that the d 15 N of NO 3 À most likely reflects the N isotopic composition of NO x sources [Freyer, 1978[Freyer, , 1991Garten, 1996;Russell et al, 1998;Xiao and Liu, 2002;Hastings et al, 2003;Heaton et al, 2004]. The important pre-industrial sources of NO x include biomass burning, biogenic soil emissions, lightning, and stratospheric injection [e.g., Wolff, 1995;Legrand and Kirchner, 1990].…”
Section: No 3 à à à Scavengingmentioning
confidence: 99%
“…The isotopic composition of NO 3 À reflects the sources and chemical processing of atmospheric NO x [Freyer, 1978;Heaton, 1986;Freyer et al, 1993;Russell et al, 1998;Xiao and Liu, 2002;Hastings et al, 2003;Michalski et al, 2003;Heaton et al, 2004]. A recent study of the isotopic composition of NO 3 À in surface snow at Summit, Greenland reveals seasonal variation in both À .…”
Section: Introductionmentioning
confidence: 99%
“…Also, volatilization of reactive nitrogen compounds from seawater and input from atmospheri c processes occur, but these fl uxes appear to be relatively small. They have been discussed in detail by Hoering (1957) and Freyer (1978).…”
Section: Nitrifying Bacteria Have Been Observed In the Open Waters Ofmentioning
confidence: 99%
“…Moore (1977) reported δ 15 N values for NH 3 -gas samples, collected close to the emission source in barnyards, of more than 20‰. However, several studies reported higher 15 N enrichment of nitrate in bulk precipitation than the co-existing am- monium (see also a review by Kendall 1998) and this was explained by the washout of 15 N depleted atmospheric NH 3 (Freyer 1978).…”
Section: N Abundance Of Needles and Fine Rootsmentioning
confidence: 99%